Development of lipid-based nanoparticles for combination treatment of pancreatic cancer with hyperthermia - Aparicio-Lopez, Cesar Benjamin (My University, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy, often asymptomatic and typically diagnosed at advanced stages. At the same time, treatment options include surgery, radiotherapy, and chemotherapy, only 20% of patients present with surgically resectable tumors. For most patients, chemotherapy remains the primary therapeutic approach, with gemcitabine, a nucleoside analog, serving as the standard of care. However, the dense fibrotic stroma, irregular blood supply, and heterogeneous tumor cell populations present significant biological and physical barriers, reducing gemcitabine’s efficacy and contributing to drug resistance. Drug delivery systems have been developed to address these obstacles by enhancing gemcitabine accumulation at the tumor site, primarily through encapsulation in long-circulating nanoparticles that exploit the enhanced permeation and retention (EPR) effect. Nevertheless, the unique architecture of PDAC tumors often limits the success of this strategy, with poor penetration and low bioactivity of gemcitabine at the tumor site remaining significant challenges. Additionally, gemcitabine’s physicochemical properties hinder effective nanoparticle loading, complicating therapeutic outcomes further. The primary objective of this dissertation is to address two major challenges in drug delivery for PDAC. First, it aims to develop gemcitabine-loaded nanoparticles that prevent drug degradation and enhance stability. Second, it aims to design these nanoparticles to be heat-sensitive, enabling controlled drug release through heat triggering mechanisms. We first designed and manufactured thermosensitive liposomes using varying ratios of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), optimizing them for minimal drug release at physiological temperature (37°C). A two-stage hot water bath setup was employed to simulate temperature-induced drug release. In the first stage, the temperature was rapidly increased, followed by a holding stage at hyperthermic levels (42°C). This setup demonstrated that the liposomes exhibited fast drug release at hyperthermia temperatures. Despite successful thermosensitive performance, the liposomes displayed low encapsulation efficiency, which is consistent with existing literature but raises concerns about cost-effectiveness. To address the limitations of nonspecific hyperthermia, we developed a novel microwave-sensitive microemulsion. Multiple ionic liquids and surfactants were screened to formulate this system. To improve biocompatibility, DPPC, DSPC, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N- [amino (polyethylene glycol)-2000] (PEG), and 1-palmitoyl-2-hydroxy-sn-glycero-3-phosphocholine (Lyso-PC) were incorporated. The final formulation included 1-butyl-3-methyl imidazolium bromide ionic liquid as the primary component, Tween 80/20 as surfactants, and ethanol-isopropyl myristate with lipids as co-surfactants. Dielectric measurements confirmed the microemulsion’s microwave sensitivity and further hyperthermia treatment demonstrated temperature-dependent cytotoxic effects in vitro. The drug delivery systems developed in this study exhibited negligible drug release at room temperature and physiological conditions (37°C) while showing effective cytotoxicity upon heat stimulation. Incorporating lipids and PEG ensured biocompatibility and stability in suspension, enhancing the potential for clinical application. This proof of concept marks a significant advancement in targeted drug delivery systems. Future improvements in gemcitabine-loaded vehicles, particularly those responsive to hyperthermia, could lead to critical clinical developments in drug delivery and hyperthermia-based treatments for PDAC.
Keywords: Pancreatic cancer; Drug delivery; Hypertermia; Lipsomes; Microemulsions